2019
DOI: 10.3390/molecules24224072
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis, Characterization, Cytotoxic Activity Assessment and Structure-Activity Relationship of 4-Aryl-6-(2,5-dichlorothiophen-3-yl)-2-methoxypyridine-3-carbonitriles

Abstract: A series of 2-methoxypyridine-3-carbonitrile (5a–i)-bearing aryl substituents were successfully synthesized in good yields by the condensation of chalcones (4a–i) with malononitrile in basic medium. The condensation process, in most cases, offers a route to a variety of methoxypyridine derivatives (6a–g) as side products in poor yields. All new compounds were fully characterized using different spectroscopic methods. Mass ESI-HMRS measurements were also performed. Furthermore, these compounds were screened for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Additional studies of the synthesis of a diverse substituted spirooxindoles via 1,3‐dipolar cycloaddition reaction are reported [12–17]. In continuation to our work [18–24], we herein report the synthesis and characterization of (1′R,2′S,7a′S)‐2′‐(2,5‐dichlorothiophene‐3‐carbonyl)‐1′‐(aryl)‐1′,2′,5′,6′,7′,7a′‐hexahydrospiro[indoline‐3,3′‐pyrrolizin]‐2‐one, I , derivatives by the reaction of the corresponding 2,5‐dichlorothiophene containing chalcone (2,5‐dichlorothiophene has not been explored extensively), l ‐proline and 2,3‐indolinedione. The molecular, crystal structure and crystal supramolecularity of three derivatives, namely, (1′R,2′S,7a′S)‐1′‐(4‐(tert‐butyl)phenyl)‐2′‐(2,5‐dichlorothiophene‐3‐carbonyl)‐1′,2′,5′,6′,7′,7a′‐hexahydrospiro[indoline‐3,3′‐pyrrolizin]‐2‐one, (1′R,2′S,7a′S)‐2′‐(2,5‐dichlorothiophene‐3‐carbonyl)‐1′‐(4‐fluorophenyl)‐1′,2′,5′,6′,7′,7a′‐hexahydrospiro[indoline‐3,3′‐pyrrolizin]‐2‐one and (1′R,2′S,7a′S)‐1′‐(3‐Chlorophenyl)‐2′‐(2,5‐dichlorothiophene‐3‐carbonyl)‐1′,2′,5′,6′,7′,7a′‐hexahydrospiro[indoline‐3,3′‐pyrrolizin]‐2‐one are also reported.…”
Section: Introductionmentioning
confidence: 72%
“…Additional studies of the synthesis of a diverse substituted spirooxindoles via 1,3‐dipolar cycloaddition reaction are reported [12–17]. In continuation to our work [18–24], we herein report the synthesis and characterization of (1′R,2′S,7a′S)‐2′‐(2,5‐dichlorothiophene‐3‐carbonyl)‐1′‐(aryl)‐1′,2′,5′,6′,7′,7a′‐hexahydrospiro[indoline‐3,3′‐pyrrolizin]‐2‐one, I , derivatives by the reaction of the corresponding 2,5‐dichlorothiophene containing chalcone (2,5‐dichlorothiophene has not been explored extensively), l ‐proline and 2,3‐indolinedione. The molecular, crystal structure and crystal supramolecularity of three derivatives, namely, (1′R,2′S,7a′S)‐1′‐(4‐(tert‐butyl)phenyl)‐2′‐(2,5‐dichlorothiophene‐3‐carbonyl)‐1′,2′,5′,6′,7′,7a′‐hexahydrospiro[indoline‐3,3′‐pyrrolizin]‐2‐one, (1′R,2′S,7a′S)‐2′‐(2,5‐dichlorothiophene‐3‐carbonyl)‐1′‐(4‐fluorophenyl)‐1′,2′,5′,6′,7′,7a′‐hexahydrospiro[indoline‐3,3′‐pyrrolizin]‐2‐one and (1′R,2′S,7a′S)‐1′‐(3‐Chlorophenyl)‐2′‐(2,5‐dichlorothiophene‐3‐carbonyl)‐1′,2′,5′,6′,7′,7a′‐hexahydrospiro[indoline‐3,3′‐pyrrolizin]‐2‐one are also reported.…”
Section: Introductionmentioning
confidence: 72%
“…and MDA-MB-231 (breast). [13] In a long list of compounds obtained through very hard synthetic work these compounds came out to be potent with IC 50 values in the range of 1-5 μM. Compound 12 was effective with IC 50 value 1.62 μM against HepG2, 13 was active against MDA-MB-231 (IC 50 1.93 μM) 14 exhibited much activity against HepG2 (IC 50 1.53 μM) and 15 exhibited outstanding antiproliferative efficiency against MDA-MB-231 (IC 50 1.38 μM), also see Table 1 for more details and comparison.…”
Section: Anticancer Agentsmentioning
confidence: 99%
“…A review of the literature has shown in several cases that amino and cyano functions can be involved in some interesting interactions with target enzymes. Indeed, various constructed heterocyclic compounds gained much attention owing to their cytotoxic and anticancer activities especially in cases wherethe NH 2 group shows conjugation when it is tethered with a pyrimidine ( Figure 2 A,B) [ 21 , 22 ] or the CN group linked in a conjugate way with a pyridine ( Figure 2 C,D) [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…anticancer activities especially in cases wherethe NH2 group shows conjugation when it is tethered with a pyrimidine (Figure 2A,B) [21,22] or the CN group linked in a conjugate way with a pyridine (Figure 2C,D) [23,24].…”
Section: Introductionmentioning
confidence: 99%